2019
DOI: 10.26650/fnjn363168
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nursing Education on Critical Thinking of Students: A Meta-Analysis

Abstract: The present study was aimed at investigating the effect of nursing education on the improvement of students' critical thinking skills in Turkey by using the meta-analysis method. Method: The literature screening was carried out in online databases using the keywords "nursing", "student", "critical thinking", "Turkey" in English and their Turkish equivalents "hemşirelik", "öğrenci", "eleştirel düşünme", "Türkiye" respectively. Quantitative studies matching the inclusion criteria were included in the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Similar results have been obtained through research on the Baccalaureate pathway in Iran (Arli et al, 2017), Kazakhstan (Babazhanova, 2020), andCanada (Profetto-McGrath, 2003). Another study in Turkey using a meta-analysis method indicated that nursing students were not able to develop their critical thinking skills (Kantek and Yıldırım, 2019). The scores predict the capacity for success in educational or workplace settings, which demand reasoned decision-making and thoughtful problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been obtained through research on the Baccalaureate pathway in Iran (Arli et al, 2017), Kazakhstan (Babazhanova, 2020), andCanada (Profetto-McGrath, 2003). Another study in Turkey using a meta-analysis method indicated that nursing students were not able to develop their critical thinking skills (Kantek and Yıldırım, 2019). The scores predict the capacity for success in educational or workplace settings, which demand reasoned decision-making and thoughtful problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…Critical thinking is widely recognized and well established in nursing education [ 1 - 3 ] because the ability to identify and assess nursing care requires critical thinking [ 4 , 5 ]. However, interventions to improve critical thinking in nursing education and ways to facilitate it among undergraduate nursing students are currently debated without definitive conclusions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding guidance models, Jayasekara et al [21] In conclusion, the existing systematic reviews and meta-analyses are limited to the development of critical thinking in nursing education (both in and outside clinical practice) without the use of technological tools [9,22,23]. Consequently, a systematic literature review is needed that focuses on critical thinking as a competency and on its development in clinical practice in nursing education through guidance and the use of technology.…”
Section: Introductionmentioning
confidence: 99%